PEMANFAATAN VIDEO ANIMASI SEBAGAI MEDIA PEMBELAJARAN DI SDN KARUNDANG 1 - Patra Aghtiar Rakhman; Reksa Adya Pribadi; Muhamad Fahrul; Mohamad Rizky Al Hakim (LPPM Universitas Cipta Mandiri, 2025)
This research aims to analyze the use of animated videos as a learning medium in improving students' listening skills at SDN Karundang 1. Listening skills are an important aspect in language learning, but many students have difficulty understanding information conveyed orally. One of the main causes of low listening skills is learning methods that tend to be monotonous and less interesting for students. Therefore, this research proposes the use of animated videos as an alternative that is more interactive, interesting, and can increase students' attention and understanding. The approach used in this research is qualitative with descriptive methods to explore the experiences and perceptions of students and teachers regarding the application of animated videos in learning. The research results show that animated videos can significantly improve students' listening skills, because this media combines visual and audio elements which make it easier for students to understand the material in a more interesting and enjoyable way. Apart from that, animated videos can also create an active learning atmosphere and encourage student learning motivation. However, this research also notes several challenges, such as limited technological facilities and technical obstacles in implementing animated videos. Overall, the use of animated videos has proven to be effective in improving students' listening skills and has a positive impact on the learning process at SDN Karundang 1, and can be used as an innovation to create a more meaningful and effective learning experience.